The Pallium Privilege of Pope Nicholas II for Archbishop Ealdred of York - Tinti, Francesca (The journal of ecclesiastical history, 2019)
The article presents and discusses the text of a little-known pallium grant of Pope Nicholas II for Archbishop Ealdred of York. Through comparison with other contemporaneous products of the papal chancery and the contents of other sources narrating the events reported in Nicholas's text, the study concludes that the papal privilege is substantially authentic. An edition, superseding a previous, late nineteenth-century one, which was based on just one of the two York manuscripts that preserve the papal privilege, is provided in the Appendix, together with a modern English translation.